The developmental trajectory of motor competence of children that lived the COVID-19 confinement period - Carballo-Fazanes, Aida (2022)
Children’s motor competence (MC) was negatively affected by the COVID-19 pandemic; however, possible chronic effects have not been studied. Therefore, the aim of this study was to examine the possible impact of the forced lack of physical activity (PA) during the COVID-19 lockdown on children’s MC two years later. The motor competence of sixty-seven healthy children (7.4–12.2 years old) was assessed using the Motor Competence Assessment (MCA). All participants completed the MCA tests at two different moments (before and after the COVID-19 lockdown), four years apart. The mean values after the COVID-19 lockdown for all participants on the subscales and on the Total MCA are lower, but no significant changes were found when controlling for gender and age (p > 0.05 in all analyses). However, a significant decrease was found in the Locomotor subscale in boys (p = 0.003). After dividing the participants into three age groups, the youngest also suffered a decrease in the Locomotor subscale (p < 0.001) and their Total MCA (p = 0.04). In addition, those participants who had a higher MC at baseline decreased their scores for the Locomotor (p < 0.001) and Manipulative (p < 0.001) subscales, and for the Total MCA (p < 0.001). In conclusion, the younger children and the more motor proficient did not fully recover from the negative effects of the pandemic lockdown after two years.